2011
DOI: 10.1111/j.1460-9568.2011.07858.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cyclin-dependent kinase-5 in the kainic acid-mediated degeneration of glutamatergic synapses in the rat hippocampus

Abstract: Increased levels of glutamate causing excitotoxic damage accompany neurological disorders such as ischemia/stroke, epilepsy and some neurodegenerative diseases. Cyclin-dependent kinase-5 (Cdk5) is important for synaptic plasticity and is deregulated in neurodegenerative diseases. However, the mechanisms by which kainic acid (KA)-induced excitotoxic damage involves Cdk5 in neuronal injury are not fully understood. In this work, we have thus studied involvement of Cdk5 in the KA-mediated degeneration of glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…CDK5 shRNAmiR induced Rac1 activation, and the subsequent lamellipodia formation was associated with BDNF release in astrocytes and induced the astrocytic neuroprotection. Various studies, most of which have utilized neurodegenerative models, have demonstrated that CDK5 suppression or inhibition favors cell viability in the presence of an insult, as ischemia, excitotoxicity and protein aggregation (Liu et al, 2003;Menn et al, 2010;Posada-Duque et al, 2015;Putkonen et al, 2011;Slevin and Krupinski, 2009;Zheng et al, 2005) Astrocytes provide trophic and metabolic support for neuronal development, maintenance of synaptic function, and neuronal survival (Allen, 2013;Parpura and Verkhratsky, 2012;Sofroniew, 2005). These results show that glutamate exerts a negative effect on cell viability and the morphology of C6 astrocyte-type cells.…”
Section: Discussionmentioning
confidence: 79%
“…CDK5 shRNAmiR induced Rac1 activation, and the subsequent lamellipodia formation was associated with BDNF release in astrocytes and induced the astrocytic neuroprotection. Various studies, most of which have utilized neurodegenerative models, have demonstrated that CDK5 suppression or inhibition favors cell viability in the presence of an insult, as ischemia, excitotoxicity and protein aggregation (Liu et al, 2003;Menn et al, 2010;Posada-Duque et al, 2015;Putkonen et al, 2011;Slevin and Krupinski, 2009;Zheng et al, 2005) Astrocytes provide trophic and metabolic support for neuronal development, maintenance of synaptic function, and neuronal survival (Allen, 2013;Parpura and Verkhratsky, 2012;Sofroniew, 2005). These results show that glutamate exerts a negative effect on cell viability and the morphology of C6 astrocyte-type cells.…”
Section: Discussionmentioning
confidence: 79%
“…Glutamate acts via different types of glutamate receptors and thereby influences cell signaling cascades and elevates intracellular calcium in neurons. Increased ER stress is linked to brain ischemia (Su and Li, 2016) and to excitotoxic injury as studied by the use of the glutamate receptor agonist, kainic acid (Sokka et al, 2007; Putkonen et al, 2011). Salubrinal that is a specific inhibitor of the eIF2α phosphatase, PP1/GADD34 (Boyce et al, 2005) and was found to protect neurons against excitotoxicity in rat hippocampus and after cerebral ischemia induced by 15 min of brain vessel occlusion in gerbils (Sokka et al, 2007; Anuncibay-Soto et al, 2016).…”
Section: Upr In Neurodegenerative Disordersmentioning
confidence: 99%
“…The synthetic liver X receptor (LXR) ligand GW3965 was used to induce Mylip/Idol (27,29), actinomycin D (Sigma) was used to inhibit gene transcription, and bafilomycin A 1 (Sigma) was used to block lysosomes. To down-regulate Mylip/Idol, freshly prepared neurons were transfected with Mylip shRNA constructs using the Nucleofector rat neuron system (Amaxa GmbH) as described previously (32,33). To modulate Mylip/Idol activity, cultured neurons were infected with adenoviruses encoding wild-type Mylip/Idol (24) for 3 days following stimulation with Reelin for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting and Immunoprecipitation-Neurons were lysed, and immunoblots were made essentially as described previously (31)(32)(33). Protein concentrations were determined using the Bradford assay, and an equal amount of protein per sample was subjected to SDS-PAGE and blotted onto nitrocellulose filters (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%